An overview on the genus Amiserica Nomura, 1974 (Coleoptera: Scarabaeidae: Melolonthinae: Sericini) - Ahrens, Dirk; Liu, Wangang; Pham, Phu Van; Fabrizi, Silvia (Zootaxa, 2021)
Here we present an overview of the species of the genus Amiserica Nomura, 1974. The taxonomy of the species of eastern Asia (China and adjacent regions) is revised herein, which so far have not been treated yet. Twenty-eight species are discovered new to science: Amiserica basisymmetrica Ahrens, Fabrizi & Liu, new species, A. belousovi Ahrens, Fabrizi & Liu, new species, A. carolusholzschuhi Ahrens, Fabrizi & Liu, new species, A. diaocangshana Ahrens, Fabrizi & Liu, new species, A. eucurviforceps Ahrens, Fabrizi & Liu, new species, A. fengyangensis Ahrens, Fabrizi & Liu, new species, A. funiushanica Ahrens, Fabrizi & Liu, new species, A. gibbosiforceps Ahrens, Fabrizi & Liu, new species, A. guanmenshanica Ahrens, Fabrizi & Liu, new species, A. guizhouensis Ahrens, Fabrizi & Liu, new species, A. gulinqin Ahrens, Fabrizi & Liu, new species, A. incisa Ahrens, Fabrizi & Liu, new species, A. jiuhuensis Ahrens, Fabrizi & Liu, new species, A. jizuensis Ahrens, Fabrizi & Liu, new species, A. linzhouensis Ahrens, Fabrizi & Liu, new species, A. longxinensis Ahrens, Fabrizi & Liu, new species, A. lucidiflava Ahrens, Fabrizi & Liu, new species, A. nahang Ahrens, Fabrizi & Liu, new species, A. panghongae Ahrens, Fabrizi & Liu, new species, A. pappi Ahrens, Fabrizi & Liu, new species, A. piaoac Ahrens, Fabrizi & Liu, new species, A. pseudoantennalis Ahrens, Fabrizi & Liu, new species, A. pseudoincisa Ahrens, Fabrizi & Liu, new species, A. sacculiforceps Ahrens, Fabrizi & Liu, new species, A. strnadi Ahrens, Fabrizi & Liu, new species, A. ventriscalptus Ahrens, Fabrizi & Liu, new species, A. venxianensis Ahrens, Fabrizi & Liu, new species, A. zhongtiaoshanensis Ahrens, Fabrizi & Liu, new species. Furthermore, our investigation resulted in two new combinations: Maladera (Eumaladera) loi (Kobayashi, 1991), new combination and Amiserica antennalis (Nomura, 1974), new combination; the first species is thus excluded from Amiserica. A key to species groups and species within groups is given, habitus and male genitalia are illustrated. The distribution of the species revised herein is shown on maps.